(untitled) - Skovbye, Tiera; Yarosh, Danika; Moriarty, Erin; 1963-; Hunt, Helen; 1963-; McNamara, Sean; Twentieth Century Fox Home Entertainment, Inc. ([Los Angeles, California], 2018)
After the tragic death of star volleyball player Caroline "Line" Found, a team of dispirited high school girls must band together under the guidance of their tough-love coach in hopes of winning the state championship.
Keywords: Drama; Grief; Drama; Drama; High school girls; Volleyball; Conduct of life; Video recordings for people with visual disabilities; Drama films; Video recordings for the hearing impaired; Sports films; Feature films; Biographical films